Money in Economic Theory - Aluko, Sam (Obafemi Awolowo University Press, 2013)
The term money refer to such commodities which serve the three-fold functions of: a recognised and acceptable medium of exchange; a standard of value or a unit of account; and, a symbol or store of wealth, both the traditional and the modern theories- and controversies about money deal with how effectively money can or should perform one or all of these three-fold functions. Furthermore, the objects that have performed these three-fold functions have themselves evolved with the development in economic thought and practice.